Genetic testing and prognosis of sarcomatoid hepatocellular carcinoma patients - Jia, Bin; Xia, Peiyi; Dong, Junqiang; Feng, Wenhao; Wang, Wenjia; Liu, Enjie; Jiang, Guozhong; Qin, Yanru (Frontiers in Oncology, 2023)
Background Sarcomatoid hepatocellular carcinoma (SHC) is a rare epithelial malignancy with high invasiveness and poor prognosis. However, the molecular characteristics and main driver genes for SHC have not been determined. The aim of this study is to explore the potentially actionable mutations of driver genes, which may provide more therapeutic options for SHC. Methods In this study, DNA extraction and library preparation were performed using tumor tissues from 28 SHC patients. Then we used Miseq platform (Illumina) to sequence the target-enriched library, and we aligned and processed the sequencing data. The gene groups were tested for SNVs/Indels/CNVs. Tumor mutation burden (TMB) was assessed by the 425-cancer-relevant gene panel. Multivariate analysis of COX’s model was used for survival analysis (OS) of patients’ clinical characteristics. Result The median overall survival (OS) of the patients was only 4.4 months. TP53, TERT, and KRAS were the top three frequently mutated genes, with frequencies of 89.3%, 64.3%, and 21.4%, respectively. A considerable number of patients carried mutations in genes involved in the TP53 pathway (96%) and DNA Damage Repair (DDR) pathway (21%). Multiple potentially actionable mutations, such as NTRK1 fusions and BRCA1/2 mutations, were identified in SHCs. Conclusions This study shows a landscape of gene mutations in SHC. SHC has high mutation rates in TP53 pathway and DDR pathway. The potentially actionable mutations of driver genes may provide more therapeutic options for SHC. Survival analysis found that age, smoking, drinking, and tumor diameter may be independent prognostic predictors of SHC.